A conceptual framework for energy security evaluation of power sources in South Korea. (15th October 2017) - Chung, Whan-Sam; Kim, Seung-Su; Moon, Kee-Hwan; Lim, Chae-Young; Yun, Sung-Won
Abstract: Due to the limited energy resources and isolated power system network, an energy security (ES) which reflects such factors as a stable energy supply, energy efficiency, and environmental protection has significance in Korea in terms of sustainable development. This study evaluated the ES in South Korea for fuel options in power generation sector (coal, nuclear, natural gas, oil, and renewables) focusing on indicators of supply reliability, economy of electricity generation, environmental sustainability, and technology complementarity. The ES indicators suggested in this study are anticipated to contribute to establishing an ES policy based on a comprehensive understanding of the ES status in South Korea. In the future, it will be necessary to establish specific scenarios for holding out regional conflicts and post-2020 climate change conventions and conduct realistic and dynamic analyses. In addition, it is essential to draw comprehensive indicators by incorporating the results from individual indicators and produce policy data regarding the priority of energy sources in terms of ES in general. This study has an unusual position in the aspect of the quantitative analysis contribution to the ES of various energy sources by the microscopic parameters together with the time series changes of ES. Highlights: A model that contributes to national energy security by energy source is proposed. Renewables, shown improve gradually, are beneficial in SS, EC and IO indicators. Nuclear, shown improve gradually too, is beneficial in GH and TC indicators. Fossil fuels such as LNG and coal have been improved in terms of indicators GH and SA. This model is expected in finding out the security enhancement factor by energy source.